2020
DOI: 10.3390/ijms21207797
|View full text |Cite
|
Sign up to set email alerts
|

Newly Synthesized Imino-Derivatives Analogues of Resveratrol Exert Inhibitory Effects in Breast Tumor Cells

Abstract: Breast cancer represents the most frequently diagnosed malignancy in women worldwide. Various therapeutics are currently used in order to halt the progression of breast tumor, even though certain side effects may limit the beneficial effects. In recent years, many efforts have been addressed to the usefulness of natural compounds as anticancer agents due to their low toxicity. Resveratrol, a stilbene found in grapes, berries, peanuts and soybeans, has raised a notable interest for its antioxidant, anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…In fact, different synthetic routes continue to be described in the literature [17][18][19]. In biological chemistry, SBs have demonstrated a broad range of biological activities [20], including antimalarial, antiproliferative [21], analgesic, anti-inflammatory [22], antiviral, antipyretic, antifungal [23] and antibacterial [24] properties (Figure 1). The imine or azomethine group (>C=N-) seems to be critical for their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different synthetic routes continue to be described in the literature [17][18][19]. In biological chemistry, SBs have demonstrated a broad range of biological activities [20], including antimalarial, antiproliferative [21], analgesic, anti-inflammatory [22], antiviral, antipyretic, antifungal [23] and antibacterial [24] properties (Figure 1). The imine or azomethine group (>C=N-) seems to be critical for their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Nature is an incredible source of drugs [28][29][30], including interesting bioactive anticancer molecules, even though they sometimes exhibit bioavailability issues that can be overcome by the use of proper vehicles or chemical modifications [31][32][33]. Concerning this, Do et al [34] reported the anticancer properties of 1-(5,7-dimetoxy-2,2dimetyl-2Hcromen-8-yl)-but-2-en-1-on (malloapelta B, malB), isolated from Mallotus apelta, which is able to inhibit the activation of nuclear factor kappa B (NF-kB) and is responsible for downregulating pivotal genes involved in inflammation.…”
Section: Contributionsmentioning
confidence: 99%
“…These compounds are at the center of interest due to their numerous pharmacological possibilities such as anticancer, antiviral, antimicrobial, antioxidant, and antineoplastic [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Coordination compounds containing such derivatives are considered to be a promising class of antineoplastic agent showing cytotoxic activity against different cell lines [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%